Comparison of Liver Biopsy Findings with the Digestive Disease Week Japan 2004 Scale for Diagnosis of Drug-Induced Liver Injury - Akemi Tsutsui; Yasuni Nakanuma; Kouichi Takaguchi; Satoko Nakamura; Hiroshi Shibata; Nobuyuki Baba; Tomonori Senoh; Takuya Nagano; Hiroko Ikeda (Mediators of Inflammation)
The liver biopsy remains a valuable tool in the diagnosis of drug-induced liver injury (DILI). The Digestive Disease Week Japan 2004 (DDW-J) scale proposed as an objective tool for the diagnosis of DILI has been widely used in Japan. So far, the histological features have not been compared with DDW-J scale in detail. Herein, we examined the correlation between liver biopsy findings and clinical features, particularly DDW-J scales. A total of 80 patients with liver injuries of unknown cause were enrolled. Based on the histological findings, these cases were categorized into 3 groups: A (DILI was strongly suspected), B (DILI was suspected), and C (DILI should be considered in the differential diagnosis). Histological groups and DDW-J scale were moderately correlated (κ=0.60). The mean total DDW-J scale scores were as follows: 4.89 for A, 3.26 for B, and 0.75 for C (p<0.05). While hepatocellular type was coincided in a majority of cases by histological and DDW-J scale evaluation, cholestatic type was not well coincided. In conclusion, biopsy findings and DDW-J scale were well correlated, and the hepatocellular type of liver injuries was well coincided by both evaluations, though there were several discrepant cases, particularly in cholestatic type.